Legal Protection Mechanisms for Child Sexual Abuse Victims: Comparative Analysis of Indonesian and United States Criminal Procedures - Saputra, Rian Prayudi; Hafiz Sutrisno (Faculty of Law, Universitas Pekalongan, 2025)
Sexual abuse against minors needs robust legislative safeguards within the criminal justice framework. The essential distinctions between civil law and common law systems result in divergent normative approaches that need comparative analysis to ascertain optimal procedures for safeguarding child victims. The objective of this study is to evaluate the efficacy of legal protections for child victims of rape by using a comparative normative analysis between the Indonesian civil law system and the American common law system, specifically within the framework of the criminal justice system. This study employs normative legal research techniques within a comparative legal analysis framework. Primary legal documents include legislation, federal and state laws, and 359 judicial rulings from the period 2019-2024. The analysis involved comparing laws at the same time using different methods, including looking at the law in context and interpreting it systematically and comparatively. Indonesia has a thorough legislative framework prioritizing restorative justice; yet, judicial execution reveals that just 34% of judgments adhere to the notion of the child's best interest. The United States exhibits more consistency (78%) in procedural protections via constitutional interpretation, notwithstanding the challenges of federal-state fragmentation. Both systems exhibit deficiencies in addressing cyber-facilitated abuse and developing technology. The efficacy of protection is contingent upon the uniformity of normative execution and the alignment of legislative and judicial practices. The convergence of legal systems is essential, with civil law embracing judicial flexibility and common law including systematic legislative methods to provide uniform child protection standards.